2019
DOI: 10.4090/juee.2019.v13n1.183197
|View full text |Cite
|
Sign up to set email alerts
|

Neural Networks for the Prediction of Fresh Properties and Compressive Strength of Flowable Concrete

Abstract: This paper presents the prediction of fresh concrete properties and compressive strength of flowable concrete through neural network approach. A comprehensive data set was generated from the experiments performed in the laboratory under standard conditions. The flowable concrete was made with two different types of micro particles and with single nano particles. The input parameter was chosen for the neural network model as cement, fine aggregate, coarse aggregate, superplasticizer, water-cement ratio, micro a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 0 publications
0
6
0
2
Order By: Relevance
“…According to Revathy et al [3], for MAPE value of less than 10% was an indication of very good performance of model and for MAPE value greater than 10%, could be due to higher variation in experimental data. The MAPE values for this research was 9.73% for the overall data, with the lowest being for training data, with 9.19% and the highest for the validation/checking data, at 12.41%.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…According to Revathy et al [3], for MAPE value of less than 10% was an indication of very good performance of model and for MAPE value greater than 10%, could be due to higher variation in experimental data. The MAPE values for this research was 9.73% for the overall data, with the lowest being for training data, with 9.19% and the highest for the validation/checking data, at 12.41%.…”
Section: Discussionmentioning
confidence: 98%
“…RHA Composition, Applicability and Effects Study by Thiedeitz et al [5] indicated specific surface area based on BET adsorption method for rice husk ash (grounded for 20 seconds with 20 Hertz frequency) and cement CEM 1 42.5R were 128 m 2 /g and 1.24m 2 /g respectively. Study by Fernandes et al [33] on RHA from thermoelectric company in Brazil, indicated mean diameter of 19.56 + 0.49 µm, specific weight of 2.22 + 0.0028 g/cm 3 and specific area of 11.35 + 0.21 m 2 /g, for RHA described in table 1. Based on Fernandes et al [33] study, the specific surface area reduced with thermal treatment temperatures.…”
Section: 1mentioning
confidence: 95%
See 2 more Smart Citations
“…Al-Swaidani and Khwies [4] research, using ANNs established in MATLAB and trained by Levenberg-Marquardt backpropagation on concrete containing volcanic-scoria as cement replacement, 0 % (control) to 35 %, indicated that ANN models were not only practical for compressive strength prediction but also highly efficient for water permeability prediction and porosity, the model performing better than multi-linear regression. Revathy et al [5] carried out a study, where mean absolute percentage error (MAPE) represented the model performance and root mean square error (RMSE) represented the error between experimental and predicted results, for neural network models generated to predict compressive strength and fresh properties of flowable concrete, using MATLAB; they used 34 data set for training, 8 for validation and 8 for testing, using BFGS quasi-newton back propagation training algorithm for neural network. Sathyan et al [6] used random kitchen sink algorithm and regularized least square algorithm; the two applications come together in the grand unified regularized least square (GURLS) tool bar in MATLAB; the training data had 32 datasets and to measure model accuracy 8 test dataset were used; hardened stages of self-compacting concrete were used for modeling.…”
Section: Introductionmentioning
confidence: 99%